Representations of cycling in metropolitan newspapers - changes over time and differences between Sydney and Melbourne, Australia - Emilsen Adrian; Bonfiglioli Catriona; Rissel Chris; Smith Ben J (BMC, 2010)
Abstract Background Cycling is important for health, transport, environmental and economic reasons. Newspaper reporting of cycling reflects and can influence public and policy maker attitudes towards resource allocation for cycling and cycling infrastructure, yet such coverage has not been systematically examined. Methods The Factiva electronic news archive was searched for articles referring to cycling published in four major metropolitan newspapers - two in Sydney and two in Melbourne, Australia, in the years from 1998 until 2008. After excluding articles not about cycling, there were 61 articles published in 1998, 45 in 1999, 51 in 2003, 82 in 2007 and 87 in 2008. Each article was coded for positive or negative orientation, and for framing of cyclists and cycling. Inter-rater reliability was calculated on a sample of 30 articles. Results Over the past decade there has been an increase in the reporting of cycling in the major newspapers in Sydney and Melbourne (from 106 in 1998/99 to 169 stories in 2007/08), with a significant increase in reporting of cycling in Melbourne, from 49 to 103 stories (p = 0.04). Recent reporting of cycling was generally positive (47% of articles, compared with 30% of articles which were negative) and focused on benefits such as health and the environment. Three quarters of negative stories involved injury or death of a cyclist. The Sydney based The Daily Telegraph reported the most negative stories (n = 60). We found positive framing of 'cycling' was more widespread than negative, whereas framing of 'cyclists' was more negative than positive. Conclusions Quantity of reporting of cycling varies over time and by newspaper, and even between newspapers in different cities owned by the same media company. News coverage appears to reflect developments in the different cities, with increases in positive reporting of cycling in Melbourne following increases in cycling in that city. Negative cycling newspaper stories may deter people from considering cycling as a transport option, but real physical or political improvements to the cycling environment may be necessary before coverage becomes more positive.